Clopidogrel, a CYP2C8 inhibitor, causes a clinically relevant increase in the systemic exposure to the active metabolite of selexipag in healthy subjects. Issue 1 (5th June 2020) - Axelsen, Lene Nygaard; Poggesi, Italo; Rasschaert, Freya; Perez Ruixo, Juan Jose; Bruderer, Shirin
Abstract : Aims: Selexipag is a prostacyclin receptor agonist approved for the treatment of pulmonary arterial hypertension. Cytochrome P450 (CYP) 2C8 is involved in the metabolism of selexipag and its active metabolite, ACT‐333679. This study evaluated the interaction of selexipag and clopidogrel, a CYP2C8 inhibitor. Methods: The study had a 2‐treatment, 1‐sequence, crossover design. Pharmacokinetics (PK) and CYP2C8 genotype were assessed in healthy male subjects administered selexipag (200 μg twice daily [b.i.d.]) alone or with clopidogrel (300 mg single dose or 75 mg once daily [o.d.]). PK modelling and simulation were conducted to support dosing recommendations. Results: Clopidogrel had a comparatively small effect on selexipag (<1.5‐fold difference in any PK variable). For ACT‐333679, the major contributor to the drug effect, the area under the plasma concentration–time curve during a dose interval and the maximum plasma concentration increased 2.25‐fold (90% confidence interval [CI] 2.06, 2.46) and 1.69‐fold (90% CI 1.55, 1.84), respectively with clopidogrel 300 mg and 2.70‐fold (90% CI 2.45, 2.96) and 1.90‐fold (90% CI 1.72, 2.11), respectively with clopidogrel 75 mg. The effect of clopidogrel on selexipag and ACT‐333679 exposure was comparable for all identified CYP2C8 genotypes. PK simulations predicted comparable exposure to ACT‐333679 following selexipag 400 μg b.i.d., 400 μg o.d. in combination with clopidogrel 75 mg o.d and 200 μg b.i.d. with clopidogrel 75 mg o.d. Conclusion: Results suggest that ACT‐333679 exposure can be maintained within the therapeutic range by reducing selexipag dosing frequency to o.d. or dose to half, when selexipag is coadministered with clopidogrel.